Brazil Gender Review : Issues and Recommendations - World Bank (Washington, DC, 2013)
The report, which documents findings of a review on gender issues in Brazil, during 1999, and updated in 2001, is responsive to the recognition of gender as an important issue in increasing socioeconomic well-being, and reducing poverty. The review examines gender in terms of demographic trends, health indicators, the effects and causes of violence, education indicators, labor market trends, and social protection. It identifies gender issues across sectors, with a view to improving the Bank's efficiency, and effectiveness, in reducing gender inequities that affect both women, and men, though discussion on male gender issues is limited. Major findings indicate that mortality rates linked to external factors (i.e., traffic accidents, homicide, suicide), differ greatly by gender; pre-natal care for pregnant women continues to be inadequate; violence continues to be high; teaching methods tend to reinforce gender segregation; and, early childhood, and education programs remain poor. Recommendations include the need for changing societal gender roles, by acting on gender issues through community, and local level organizations, but targeting men as well as women, since male issues, such as violence and under performance in school, among others, may be attributed to men's narrowly defined gender roles, while effective women's programs, often require men's implicit, or explicit cooperation, and involvement.